Enhancing Post-Operative Recovery in Spastic Diplegia through Physical Therapy Rehabilitation following Selective Dorsal Rhizotomy: A Case Report and Thorough Literature Analysis - Jawaria Shahid; Ayesha Kashif; Muhammad Kashif Shahid (MDPI AG, 2023)
Spasticity is a common issue among children, especially those with bilateral spastic cerebral palsy (CP). Selective dorsal rhizotomy (SDR) is a surgical procedure that is often used to decrease lower limb rigidity, alongside other treatment options such as intrathecal medication, peripheral nerve surgery, and deep brain stimulation (DBS). The objective of these therapies is to improve the standard of living for young individuals. This article intends to explain the motor deficits observed in spastic diplegia and a rehabilitation program using physical therapy after SDR. The information can help with counseling parents about the prognosis and developing a clinical treatment plan. The article presents a case study of a 12-year-old girl who recently underwent L3, L4, and L5 nerve root rhizotomy in the physical therapy department. It highlights the importance of long-term physical therapy follow-up and orthotic usage in the management of spastic diplegia.